Band saw and circular saw: current utilization in woodworking industry / Mohd Ikram Ariffin - Ariffin, Mohd Ikram (2003)
People are starting to use the saw since 60,000 years ago. But the first band saw appeared in woodworking industry in 1808 while in the first circular saw was produced around 1800. Then in the modem days these two machines are improved with many addition of accessories. Nowadays we can see many types of the band saw and circular saw machines, but these machines are similar basically to the first time it was invented. There is not much development on the machines, only in saw blade, saw tip and design of new tooth pattern. The power of the machine also increased. With this invention, the development of the saw teeth will increase the new uses of both machines.